Gratis Ongkir dan Paylater terhadap Pembelian Impulsif Mahasiswa Gen Z: Peran Moderasi Gaya Hidup - Vahera, Anyelir Aliya; Wuryanti, Lestari; Mufahamah, Euis (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2025)
This study’s purpose is identifying lifestyle role factors that influencing free shipping impact and Paylater on impulsive purchases made by Generation Z students. Midwifery Study Program students at Malahayati University (Intake of 2019–2023) participated as respondents. This study analyzed 129 surveys. The research data was analyzed using quantitative methods and hypothesis testing, that used the MRA test using analysis tools which is IBM SPSS. This study has results that free shipping with t-value 2.252> t-table 1.984 and 0.000 <0.05 significant value on impulsive buying behavior, Paylater has a t-value of 5.923> t-table 1.984 and a significance value of 0.000 <0.05 on impulsive buying behavior, Free shipping and Paylater have a simultaneous or joint effect on Impulsive Buying behavior, Lifestyle has an moderate ability to influence free shipping variables on Impulsive Buying Behavior, Lifestyle is able to moderate the influence of Paylater variables on Impulsive Buying Behavior. Free shipping influence variables, Paylater on Behavior of Impulsive Buying after a moderating variable presence (Lifestyle) is 62.6%. These findings support modern consumer behavior theories that emphasize the importance of psychological and lifestyle aspects in influencing purchasing decisions in the digital era.